Development of Short Story Writing with Religious Values through Problem-Based Learning - Oktaviani, Reni; Chan, Sam Mukhtar (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
This research is about post-pandemic learning that changes online learning patterns to hybrid or offline. As a material for developing creativity, reading materials that are easy to understand and easy to use as references in writing are needed. Writing skills in stringing words are needed to produce quality writing. For most, writing in accordance with the Improved Spelling is not necessary. This is not justified and needs to be reviewed further, especially for students who choose the Indonesian Language and Literature Education Study Programme. Writing skills are needed in the learning process, especially in the Popular Writing Skills course. This research uses research and development. Students can start from the type of fiction story to make it easier to write it. There are various kinds of fiction stories such as novels, fairy tales, short stories, and others. Short stories are easier to make because the problems that occur are around.